2009
DOI: 10.1007/s11661-008-9727-7
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Converting Dilatometric Strain Measurements to the Fraction of Phase Formed during the Transformation of Austenite to Martensite in Powder Metallurgy Steels

Abstract: A model is developed to allow converting dilatometric strains that occur during the continuous cooling transformation (CCT) of austenite to martensite to volume fraction martensite formed in powder metallurgy steels. Unlike existing models, this model can accurately account for the observed decrease in the measured transformation strain with increased porosity. As a demonstration, the model is used to accurately calculate the volume fraction of martensite formed during the CCT of austenite to martensite in FL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…[16][17][18] Good agreement between the measured and calculated volumes of martensite was confirmed when the effect of the alloying element was considered (called the "AE" calculation). Similarly good correspondence has been observed in the previous models [2][3][4][5][6][7][8] used for heat-treatable low-alloy steels when the alloying elements are considered. The other calculation performed (called the "CE" calculation) considered only the carbon effect on the lattice parameters without any other alloying effects, and is shown in Eqs.…”
Section: Notesupporting
confidence: 83%
See 1 more Smart Citation
“…[16][17][18] Good agreement between the measured and calculated volumes of martensite was confirmed when the effect of the alloying element was considered (called the "AE" calculation). Similarly good correspondence has been observed in the previous models [2][3][4][5][6][7][8] used for heat-treatable low-alloy steels when the alloying elements are considered. The other calculation performed (called the "CE" calculation) considered only the carbon effect on the lattice parameters without any other alloying effects, and is shown in Eqs.…”
Section: Notesupporting
confidence: 83%
“…Dilatometric analysis has been widely used for determining quantitative volume fractions of transformed phases, and many investigations have provided analytical models for converting dilatometric data into volume fractions of the constituent phases. [2][3][4][5][6][7][8] However, most of these previous models have been mainly focused on heat-treatable low-alloy steels whose total amount of alloying element is below 5 wt%. The principle used in these models for dilatometric analysis is based on the relative atomic volume change between parent phase and transformed phase.…”
mentioning
confidence: 99%
“…15) Warke et al reported that the M s temperature increased as the relative density in the sintered PM steel decreased. 16) Thus, the occurrence of auto-tempering during quenching of the sintered S55C sample is possible although the carbon content in the S55C sample (0.55 mass%) is high enough to lower the M s temperature and to suppress the occurrence of auto-tempering. Figure 1(b) shows the microstructure of tempered martensite with numerous carbide particles, which are uniformly dispersed in the matrix after tempering at 550°C for 600 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have reported predictions of volume fraction of transformed phase(s) by using the dilatometric transformation strain measured by evaluating the volume strain difference between parent phase and transformed phase, based on atomic lattice parameter calculations. These approaches are termed models for analyzing dilatometric behavior or conversional models of transformation strain.…”
Section: Introductionmentioning
confidence: 99%
“…Warke et al [11] modified a conversional model for martensite transformation to consider porosity in powder metallurgy steel.…”
Section: Introductionmentioning
confidence: 99%